You can factor out an x:
x (
- 2)
Now set x equal to zero and the expression in the parentheses equal to zero
x = 0
![x^(2) - 2 = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/oz8wa9h8ddsnh3tenhvdlgx3jutxqd0act.png)
We don't need to do anything to x = 0 because x is already isolated, but you can further isolate x in the equation:
x^2 - 2 = 0
To do this add 2 to both sides
x^2 = 2
Take the square root of both sides to completely isolate x
x = ± √2
The zeros are:
0 and ±√2
Hope this helped!
~Just a girl in love with Shawn Mendes